How to foster agroecological innovations? A comparison of participatory design methods - Berthet, Elsa T.A.; Barnaud, Cécile; Girard, Nathalie; Labatut, Julie; Martin, Guillaume (Journal of environmental planning and management, 2016)
Facing contemporary environmental crisis implies fostering agroecological innovations that take into account local ecological regulations and rely on multiple stakeholders' innovation capacities. This paper draws on two fields of literature that remain unconnected so far: participatory approaches and design sciences. It proposes an analysis grid to support a reflexive analysis of cases of implementation of three participatory design methods: ComMod (Companion Modelling for concerted management of natural resources), Forage Rummy (simulation-based board game for designing farming systems) and KCP (collective design workshops to foster innovation). This analysis highlights key features of the methods in view of agroecological innovation challenges, focusing on knowledge management and organisation for exploration.